The 1st and 2nd Battalions The Sherwood Foresters (Nottinghamshire and Derbyshire Regiment) in the Great War. - Wylly, H. C. (Andrews UK, 2011)
In this history the two battalions are dealt with separately but the list of Honours and Awards combines both battalions. When war broke out the 1st Battalion was in Bombay and sailed for home on 3 Sep 1914, arriving on 2 October and joining the newly formed regular division, the 8th. They landed in France on 5 November 1914 taking part in the battles of Neuve Chapelle, Aubers Ridge and Loos. Both the regiment's VCs were won by the 1st Battalion, at Neuve Chapelle and during the Aubers Ridge ...